Effectiveness of Low Level Laser in the Treatment of Carpal Tunnel Syndrome - Abid Ali, Shawqi J.; Ja’afar, Isra’a F.; Hasan, Zeki N. (Journal of the Faculty of Medicine Baghdad, 2012)
Background: Carpal tunnel syndrome (CTS) is one of common peripheral nerve disorder which involves an entrapment neuropathy of the median nerve at the wrist which occurs either due to primary idiopathic cause or secondary to systemic causes. The diagnosis of CTS is clinical and supported by neurophysiological analysis. Surgical intervention is the main treatment modality. Objective: The aim of the present study is to evaluate the effectiveness of low level laser therapy (LLLT) to treat mild – moderate CTS cases. Pateients and methods: The study involves 60 symptomatic patients complaining of CTS were divided into two groups. Group A was subjected to real LLLT by Gallium – Arsenide (Ga-As) laser (904 nm), whereas group B was subjected to sham laser. Thirty asymptomatic normal individuals as group C were subjected to real LLLT in the same protocol as that applied to CTS cases. The individuals were evaluated clinically and by nerve conduction studies (NCSs) at early time as baseline reading and immediately after the treatment and later on after two weeks from stopping the treatment sessions. Results: LLLT showed significant pain reduction (70.9%) and improved latency and amplitude studies for sensory (16.7% and 29%, respectively) and motor (18% and 26%, respectively) median nerve fibers in patients group who were exposed to real laser therapy in comparison to sham group but normal individuals showed significant increment in motor amplitude (12%) after completing therapy sessions. Conduction velocity and minimal F wave latency studies did not show significant changes in all study groups. Conclusion: LLLT is proved to be an effective, easy, handy, relatively safe, and noninvasive treatment modality for idiopathic CTS of mild – moderate severity. Broadening the spectrum of wavelengths and changing the power density and energy doses and enrolment of cases which has already been treated surgically still a hopeful view of using LLLT in CTS treatment for further investigations.